Pengujian Sistem Informasi Pendaftaran Job Fair di Institut Widya Pratama dengan teknik Equivalence Partitioning - Maulana, Mohammad Reza; Muhammad Faizal Kurniawan; Wahyu Setianto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Institut Widya Pratama (IWIMA) continuously strives to produce high-quality graduates. To provide better opportunities for its graduates, IWIMA routinely organizes job fairs to connect job seekers with potential employers. One of the challenges in conducting these events is the registration and data management process for job seekers. To address this issue, IWIMA developed a job fair registration information system for job applicants. A comprehensive testing process is essential to ensure the system functions effectively and efficiently. One of the techniques that can be used for system testing is equivalence partitioning. This technique ensures that the input and output align with the application design by applying predefined testing scenarios. The research stages include designing the testing process, conducting the tests, recording the results, and evaluating the outcomes. In the initial research stage, the testing design is developed by generating use cases, test parameters, test partitions, test data, and test cases. Subsequently, from the system testing conducted across seven test cases, the results indicate that the information system operates effectively as expected. However, based on the evaluation and analysis, it is recommended to further enhance the quality of the information system. These recommendations can serve as a reference for future system development.